CNT-based tapered optical fiber for ethanol remote sensing over 3-km optical fiber - Khalaf, Ahmed Lateef; Hasan, Taif Sami; Abdulbari, Hayder A.; Kadhim, Wafaa A.; Mohd Hanif, Yaacob (Elsevier, 2021)
Certain organic liquids like ethanol in water are considered hazardous and have an enormous environmental impact since it is toxic and classified as class I flammable liquids. Remote sensing with complex sensors is a common technique for detecting and tracking spillages of hazardous spillages. Most of the applied remote sensing methods suffer from location and control issues that force the user to be at the exact sensing spot during operation. The present work introduces a simple and highly sensitive tapered multimode optical fiber (TMOF) sensor coated with carbon nanotubes (CNT) for flammable liquids remote sensing applications. The new proposed sensor ability to transfer signals to a remote data collection center of about 3 km from the sensor location was investigated. Ethanol was utilized as the index solution to be tested in the present work. The proposed sensor was attached to 3 km multimode silica optical fiber and characterized towards different concentrations of ethanol in de-ionized water at room temperature. Various characterization techniques have investigated the detailed structural properties of the sensing layer. The experimental results demonstrated that the proposed remote sensor exhibits rapid response with recovery times of 8.7 s and 18 s, respectively, and relative absorbance of 26% upon exposure to 100% ethanol. The sensor attains an overall sensitivity of 1.3/vol% towards low ethanol concentrations in water (0.01–0.5%). Besides, the optical sensor manifests outstanding repeatability when exposed to another cycle of ethanol with concentrations of 20% and 40% in de-ionized water. The proposed optical remote sensor's superior performance via low cost and simple techniques indicates its high efficiency for ethanol detection in various industrial applications.